Modern Problems of Obtaining Low Water Demand Fasteners - Karimov G.U; Allamov CH.M; Soliev Sh.J; Ismatulloev F.Z. (Genius Journals, 2022)
The article describes methods for obtaining effective dry mixes based on binders of low water binders (LWB) for the production of cellular concrete. Ways of solving problems are given by mathematical planning of the experiment. Systematic dependences were established on the composition of the components and the intensity of the grinding process of the dry mix for cellular concrete.
Keywords: Concrete; Admixture; Super Plasticizer; Increase In Mobility